Effect of different doses of nitrogen fertilizing on the grain and fodder productivity of winter rye varieties in the conditions of the Republic of Mari El - V. A. Maksimov; R. I. Zolotareva; R. B. Maksimova (Аграрная наука Евро-Северо-Востока)
The results of the study of new winter rye varieties based on a set of economically valuable traits on sodpodzolic soils of the Republic of Mari El are provided. The varieties of domestic breeding (Tatiana - control, Moscovskaya 15, Rada, Yantamaya) participated in the trial against the background of the basic application of N24P24K24 at various levels of nitrogen nutrition (N0, N45 in spring with renewal of vegetation, N15in the earing phase, N45 in spring with renewal of vegetation + N15 in the earing phase). So, Rada variety significantly exceeded the control variant (Tatiana variety) by 0.94 t/ha. Below the standard were Moscovskaya 15 and Yantarnaya varieties. If the latter showed a tendency to decrease the yield (by 0.33 t/ha), Moscovskaya 15 was 0.8 t/ha lower than the control. Different options of nitrogen fertilizing significantly increased grain and fodder yield. The maximum value of these indicators is noted when applying nitrogen fertilizers in a dose of N45 (in spring with the renewal of vegetation) + N15 (during the earing phase). The application of mineral nutrition increases the cost of grain production. According to the results of the economic analyses the lowest cost price (2.9 rubles/kg) and the highest profitability rates were noted when cultivating Rada variety on variants with application of N45 into fertilizing (188.0%) and N15 into top dressing during the earing phase (192.3%). The introduction of nitrogen fertilizing in these variants against the background of the main application of azophoska in a dose of 1.5 dt / ha led to an increase in the cost of one kilogram of grain to 3.3 rubles, but it was still highly profitable (the profitability levels of grain production were 157% and 156% respectively).